(25-2x)(15-2x)=225

Simple and best practice solution for (25-2x)(15-2x)=225 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (25-2x)(15-2x)=225 equation:


Simplifying
(25 + -2x)(15 + -2x) = 225

Multiply (25 + -2x) * (15 + -2x)
(25(15 + -2x) + -2x * (15 + -2x)) = 225
((15 * 25 + -2x * 25) + -2x * (15 + -2x)) = 225
((375 + -50x) + -2x * (15 + -2x)) = 225
(375 + -50x + (15 * -2x + -2x * -2x)) = 225
(375 + -50x + (-30x + 4x2)) = 225

Combine like terms: -50x + -30x = -80x
(375 + -80x + 4x2) = 225

Solving
375 + -80x + 4x2 = 225

Solving for variable 'x'.

Reorder the terms:
375 + -225 + -80x + 4x2 = 225 + -225

Combine like terms: 375 + -225 = 150
150 + -80x + 4x2 = 225 + -225

Combine like terms: 225 + -225 = 0
150 + -80x + 4x2 = 0

Factor out the Greatest Common Factor (GCF), '2'.
2(75 + -40x + 2x2) = 0

Ignore the factor 2.

Subproblem 1

Set the factor '(75 + -40x + 2x2)' equal to zero and attempt to solve: Simplifying 75 + -40x + 2x2 = 0 Solving 75 + -40x + 2x2 = 0 Begin completing the square. Divide all terms by 2 the coefficient of the squared term: Divide each side by '2'. 37.5 + -20x + x2 = 0 Move the constant term to the right: Add '-37.5' to each side of the equation. 37.5 + -20x + -37.5 + x2 = 0 + -37.5 Reorder the terms: 37.5 + -37.5 + -20x + x2 = 0 + -37.5 Combine like terms: 37.5 + -37.5 = 0.0 0.0 + -20x + x2 = 0 + -37.5 -20x + x2 = 0 + -37.5 Combine like terms: 0 + -37.5 = -37.5 -20x + x2 = -37.5 The x term is -20x. Take half its coefficient (-10). Square it (100) and add it to both sides. Add '100' to each side of the equation. -20x + 100 + x2 = -37.5 + 100 Reorder the terms: 100 + -20x + x2 = -37.5 + 100 Combine like terms: -37.5 + 100 = 62.5 100 + -20x + x2 = 62.5 Factor a perfect square on the left side: (x + -10)(x + -10) = 62.5 Calculate the square root of the right side: 7.90569415 Break this problem into two subproblems by setting (x + -10) equal to 7.90569415 and -7.90569415.

Subproblem 1

x + -10 = 7.90569415 Simplifying x + -10 = 7.90569415 Reorder the terms: -10 + x = 7.90569415 Solving -10 + x = 7.90569415 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + x = 7.90569415 + 10 Combine like terms: -10 + 10 = 0 0 + x = 7.90569415 + 10 x = 7.90569415 + 10 Combine like terms: 7.90569415 + 10 = 17.90569415 x = 17.90569415 Simplifying x = 17.90569415

Subproblem 2

x + -10 = -7.90569415 Simplifying x + -10 = -7.90569415 Reorder the terms: -10 + x = -7.90569415 Solving -10 + x = -7.90569415 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + x = -7.90569415 + 10 Combine like terms: -10 + 10 = 0 0 + x = -7.90569415 + 10 x = -7.90569415 + 10 Combine like terms: -7.90569415 + 10 = 2.09430585 x = 2.09430585 Simplifying x = 2.09430585

Solution

The solution to the problem is based on the solutions from the subproblems. x = {17.90569415, 2.09430585}

Solution

x = {17.90569415, 2.09430585}

See similar equations:

| 8x-(2+5)= | | -2(x+3)=x-3 | | 3t^(1/2)=4 | | 17u-24=10 | | cos=14/25 | | x/15=83 | | -3w-2=-14 | | 50x+20y=450 | | -87+6x=33 | | -7x-2.8=6x-3.2 | | 8x-2x+x=-5 | | 2x=l-3p | | ×/3-9=1 | | 0.254c-4.331=56.456c | | K+6=J | | x-8.82=3.26 | | -6x-3=x^4+2x^3+2x^2+2x+1 | | 49x^10+x^3-5=0 | | -2(-y+4)+(y-13)= | | 6.1(6.3-3.4h)=4+3(3.9h-1) | | -(1+7m)-6(-7-m)=36 | | 2.3(7.24p-2.7)=5.7-2(p+8.1) | | 6n-18=4(n-3) | | 7(x+7)=0 | | 4.23(m-4.8)=2.56(m+7.91) | | -114+15x=51 | | -2-y+2+y-13= | | 15/3.5=y/9 | | 2tan^2x=3tanx+1 | | (y+3)+3y=3 | | (X-8)+(9x+2)+36=360 | | 2tan(2x)=3tanx+1 |

Equations solver categories